Green synthesis of silver NPs using aqueous extract of Artemisia scoparia for hydrogenation of aromatic nitro compounds and their biological activity - Bhati, Prashant; Tiwari, Richa; Kothari, S. L.; Ray, Khushi; Lamba, Narendra Pal; Kumar, Yogesh; Binsuwaidan, Reem; Saeed, Mohd; Obaidur, Safia; Srivastava, Sonia Chahar; Sambhav, Kumar; Chauhan, Manmohan Singh (Frontiers in Microbiology, 2025)
The green synthesis of silver nanoparticles (AgNPs) using Artemisia scoparia (A. scoparia), a plant abundant in bioactive compounds, provides an eco-friendly, cost-effective, and sustainable method for nanoparticle synthesis. Silver ions were successfully reduced using an aqueous extract of A. scoparia, resulting in AgNPs with a characteristic UV–visible absorption peak at 421 nm. Comprehensive characterization using FTIR, TEM, SEM, and DLS confirmed their stability, uniform morphology, and functional groups. The antibacterial activity of the synthesized AgNPs was evaluated against E. faecalis and P. aeruginosa, and their catalytic activity was assessed by reducing aromatic nitro compounds. A. scoparia-derived AgNPs demonstrated potent antibacterial activity, effectively inhibiting the growth of E. faecalis and P. aeruginosa, indicating potential for addressing antibiotic-resistant bacteria. Additionally, these AgNPs exhibited remarkable catalytic efficiency in reducing aromatic nitro compounds, showcasing their potential as eco-friendly catalysts. This dual functionality highlights their significant role in sustainable nanotechnology and environmental remediation efforts.